PERAN RUMAH SAKIT SEBAGAI PENGENDALI DATA DALAM MENJAMIN KEAMANAN DATA PRIBADI PASIEN PADA SISTEM KESEHATAN DIGITAL - Gunawan Widjaja; Wagiman; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. Adiba Aisha Amira, 2025)
Digital transformation in the health sector has brought various conveniences and efficiencies in patient data management, but it has also posed new challenges related to data security and privacy. Hospitals play an important role as data controllers responsible for ensuring that every process of collecting, storing, processing, and distributing patient data remains in accordance with the principles of security and confidentiality. This study aims to analyse the role of hospitals as data controllers in ensuring the protection of patient personal data in digital health systems, as well as to identify challenges and control strategies. The study was conducted through a literature review of various journals, regulations, and reliable documents, using a descriptive-qualitative approach. The results of the study indicate that data protection requires collaboration between the implementation of security technologies (encryption, two-factor authentication, audit trails), compliance with regulations, standardisation of operational procedures, and improvement of digital literacy among human resources. The main challenges include cyber threats, infrastructure and human resource limitations, and suboptimal data security culture. Systematic and continuous efforts in strengthening policies, education, and internal supervision are key to the success of hospitals as data controllers in the evolving era of digital health.